2015
DOI: 10.1007/s00213-015-4022-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute ketamine challenge increases resting state prefrontal-hippocampal connectivity in both humans and rats

Abstract: This translational comparison demonstrates a cross-species consistency in pharmacological effect and elucidates ketamine-induced alterations in PFC-HC coupling, a phenotype often disrupted in pathological conditions, which may give clue to understanding of psychiatric disorders and their onset, and help in the development of new treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 85 publications
2
73
0
Order By: Relevance
“…[26] Immediately (minutes to hours) after administration of ketamine, the amplitude of BOLD signal fluctuations[29] and FC[23] was observed to increase , although the amplitude of task-evoked responses was reduced. [39] Chronic administration (greater than 24 hours) of ketamine focally reduced FC in selected RSNs.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Immediately (minutes to hours) after administration of ketamine, the amplitude of BOLD signal fluctuations[29] and FC[23] was observed to increase , although the amplitude of task-evoked responses was reduced. [39] Chronic administration (greater than 24 hours) of ketamine focally reduced FC in selected RSNs.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy subjects, functional connectivity between the rACC and mPFC increased acutely (95) and decreased 24 hours after ketamine infusion (96). Furthermore, using PET imaging methods, ketamine associated with increased glucose metabolism in the dorsal ACC (dACC) (97), altered glucose metabolism in PFC regions (9799) in MDD, and increased glucose metabolism in the dACC and putamen in BD patients (100).…”
Section: Ketamine and Functional Neural Circuitry In Depressionmentioning
confidence: 99%
“…Another study by Grimm et al (2015) investigated ketamine-induced changes in functional connectivity specifically between the dlPFC and hippocampus. They found that acute ketamine administration increased dlPFC-hippocampus connectivity in both healthy human subjects and in rats.…”
Section: Pharmacological Imaging and The Behavioral Effects Of Ketaminementioning
confidence: 99%